Management of coopetitive tensions in SMEs of the Ecuadorian agro-industrial sector: Conflicts, rivalries, and interests - Jimmy Gabriel Díaz-Cueva; Rubén Guevara-Moncada (Cogent Business & Management, 2023)
The purpose of the research was to identify the sources of tensions, the factors that determine their magnitude and the circumstances that influence the management of said tensions in the context of coopetitive interactions between SMEs belonging to the agro-industrial sector of Ecuador. In the study, carried out with a qualitative approach using multiple case studies and grounded theory, 25 cases of companies belonging to the banana, cocoa, shrimp, and flowers subsectors of that country were included, in which 54 executives and 15 management experts participated strategic. The results indicate that the tensions and conflicts that occur in coopetitive relationships derive from unilateral factors associated with the organization, and from multilateral factors associated with the sector or the market. The study highlights the importance of strengthening the ability to manage tensions and conflicts that occur between companies that compete and collaborate simultaneously to increase the perceived value of the customer and the network, even in the presence of conflicts, rivalries, and divergent interests. This implies that interested parties must be able to deploy new inter-business interactions based on trust, mutual respect, and recognition of legitimate interests, with the aim of sharing resources, reducing costs, and taking advantage of new business opportunities. The novelty of the research lies in the fact that it is the first study that addresses, from an empirical perspective, the way in which the coopetitive paradox manifests itself in Ecuadorian SMEs.
Keywords: 650; contradictions; coopetition; coopetitive paradox; coopetitive tensions; dualities